2015
DOI: 10.1111/head.12651
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Underpinnings of Sensory Hypersensitivity in Migraine: Insights from Neuroimaging and Electrophysiological Studies

Abstract: Whereas considerable data have been generated about the pathophysiology of pain processing during migraine attacks, relatively little is known about the neural basis of sensory hypersensitivity. In migraine, the term "hypersensitivity" encompasses different and probably distinct pathophysiological aspects of sensory sensitivity. During attacks, many patients have enhanced sensitivity to visual, auditory and/or olfactory stimuli, which can enhance headache while interictally, migraineurs often report abnormal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 134 publications
2
53
0
Order By: Relevance
“…These regions are involved with both pain nociception circuitry and the limbic system, which has been previously implicated in the perception of pain in adult patients with MTH at the functional, mechanistic, and electrophysiologic levels. 16,17 The involvement of TTH abnormalities, which was unexpected, indicates that diffusion abnormalities in the hippocampus and thalamus may potentially reflect enhanced pain circuitry as opposed to intrinsic pathophysiologic differences between MTH and TTH. This study is the first to describe early ADC diffusion changes in several areas involved in the limbic circuit in pediatric patients with MTH and TTH.…”
Section: Discussionmentioning
confidence: 99%
“…These regions are involved with both pain nociception circuitry and the limbic system, which has been previously implicated in the perception of pain in adult patients with MTH at the functional, mechanistic, and electrophysiologic levels. 16,17 The involvement of TTH abnormalities, which was unexpected, indicates that diffusion abnormalities in the hippocampus and thalamus may potentially reflect enhanced pain circuitry as opposed to intrinsic pathophysiologic differences between MTH and TTH. This study is the first to describe early ADC diffusion changes in several areas involved in the limbic circuit in pediatric patients with MTH and TTH.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with migraine also commonly experience photophobia, phonophobia, and CA between attacks and demonstrate lower discomfort thresholds to visual, auditory, and tactile stimuli in the interictal period compared to non‐migraine controls . Functional neuroimaging studies have found that people with migraine have greater response to visual stimuli in the visual cortex and in visual association areas, and it is believed that this brain hyper‐responsiveness may relate to symptoms of photophobia . Interictal photosensitivity in patients with migraine is associated with brain structural aberrations, including greater cortical thickness in the left fronto‐parietal and right parietal‐occipital regions .…”
Section: Introductionmentioning
confidence: 99%
“…Patients with migraine also demonstrate increased interictal connectivity between auditory and visual cortices and the anterior insula, which is involved in emotional salience; this may in part explain the heightened sensitivity to visual and auditory stimuli in migraine . CA, another form of sensory hypersensitivity, is likely related to sensitization of pain processing and modulating regions including first‐order and second‐order trigeminovascular neurons and thalamic nociceptive neurons …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations